General education: Learning from the past, preparing for the future - Karen Gersten (Laureate Education Inc, 2012)
This article explores the widening gap between business and societal needs and current general education curricula. Research is presented that documents gaps between projected needs of industry and current practices in postsecondary education especially in the general education areas. Positive efforts to close the gap are highlighted. Also highlighted are changing regulatory environments, some that support forward-thinking approaches to liberal education and others that revert to traditional educational practices. With a focus on adaptability and intentional teaching and learning, recommendations are presented for flexible curriculum, intentional pedagogy, and a backwards approach to the teaching-learning enterprise that begins with authentic assessment of student learning. DOI: 10.18870/hlrc.v2i2.67